He Lu zhi si: 1831 nian zhenhan quanqiu de yiliao shijian 何魯之死：1831年震撼全球的醫療事件 [The Death of Hoo Loo: The Medical Event in 1831 that Shocked the Globe]: by 高晞 Gao Xi - Gao, Yiyang (Journal of the European Association for Chinese Studies, 2025)
He Lu zhi si: 1831 nian zhenhan quanqiu de yiliao shijian 何魯之死：1831年震撼全球的醫療事件 [The Death of Hoo Loo: The Medical Event in 1831 that Shocked the Globe] By 高晞 Gao Xi 北京市：中華書局 [Beijing: Zhonghua Publishing House], 2024. 270 pp. ISBN: 9787101166682